2010
DOI: 10.1155/2010/642379
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Scan Statistics Adjusted for Multiple Clusters

Abstract: The spatial scan statistic is one of the main epidemiological tools to test for the presence of disease clusters in a geographical region. While the statistical significance of the most likely cluster is correctly assessed using the model assumptions, secondary clusters tend to have conservatively highP-values. In this paper, we propose a sequential version of the spatial scan statistic to adjust for the presence of other clusters in the study region. The procedure removes the effect due to the more likely clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(50 citation statements)
references
References 27 publications
0
50
0
Order By: Relevance
“…We present results of the multiple cluster Kulldorff method 14 using both income unadjusted and adjusted expected counts. We set the highest proportion of the population a zone can contain at 15%, the α -cutoff to declare significance at α = 0.05 and simulate 9,999 Monte Carlo realizations under the null hypothesis of no clusters.…”
Section: Brain and Breast Cancer In Western Washingtonmentioning
confidence: 99%
See 2 more Smart Citations
“…We present results of the multiple cluster Kulldorff method 14 using both income unadjusted and adjusted expected counts. We set the highest proportion of the population a zone can contain at 15%, the α -cutoff to declare significance at α = 0.05 and simulate 9,999 Monte Carlo realizations under the null hypothesis of no clusters.…”
Section: Brain and Breast Cancer In Western Washingtonmentioning
confidence: 99%
“…This approach is therefore not using the correct reference distribution. The most recent multiple cluster version of the Kulldorff method 14 removes the significant zone, and then repeats the procedure now using a new reference distribution, until no more significant zones are found. A deficiency of this approach is that the p -values are not directly comparable since they are based on different sample sizes and hence have different power.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improvements to wellestablished methods such as SatScan have been developed (Zhang, Assunção, and Kulldorf 2010). However, much effort has focused on innovative Bayesian methods.…”
Section: Statistical Analysis and Modelling Of Local Clustersmentioning
confidence: 99%
“…Some recent methods more rigorously account for multiple clusters in the detection process. Zhang et al (2010) propose assessing secondary clusters after sequential deletion of observed data inside the previously detected clusters, essentially a variant of more traditional forward stepwise variable selection. Li et al (2011) propose a modified scan statistic that evaluates the most likely two (or more) clusters rather than the single most likely cluster.…”
Section: Introductionmentioning
confidence: 99%